Character Education at Tomohon Music Studio Education and Skills Institution (LPK): Overview of Character Education Dimensions From Doni Koesoema Albertus - Kaeng, Stevanus; Sumual, Shelty D. M.; Tuerah, Roos M. S. (Technium Social Sciences Journal, 2022)
The primary purpose of this study is to examine and describe: (1) Character Education Planning at LPK JT Music Studio Tomohon based on a review of Character Education Dimensions, (2) Implementation of Character Education at LPK JT Music Studio Tomohon based on a review of Character Education Dimensions, (3) Evaluation of Character Education at LPK JT Music Studio Tomohon based on a review of the Character Education Dimensions. This study uses a qualitative descriptive method by describing the state of the status of social phenomena to obtain conclusions. Observation, interviews, and documentation carried out the data collection procedure. The main instruments in data collection are field notes, recording tools, and documentation in the form of photos or pictures. The situation of this institution tends not to optimize and facilitate educational programs due to a lack of planning, understanding, and methods used. Institutions are limited to running training programs and courses oriented to competence and knowledge and lacking in character building. The community of both students and educators does not prioritize character education development programs. This does not bring students to appreciate and practice the values and virtues based on the review of the Character Education Dimensions. (2) In management, every plan will lead to assessment and evaluation. And this is very helpful for developing future character education programs at LPK JT Music Studio Tomohon. Students live from the stage of values and virtues and then imbue them with reflection material for students. Students do not get enough space, and LPK JT Music Studio Tomohon does not facilitate so that students do not reach the Reflection stage. (3) character education that does not provide good planning and evaluation indicates symptoms that are not by the values and virtues in the Educational Dimension Character. Value Reflection, which is the hope of developing attitudes and actions, has not been implemented.